In Particular Issues Of Term And Terminology - Khosiyat Abdukakhhorova (Euro Asian Journal Publishing, 2024)
The article provides information about terms and terminology issues, the development of terminology, the characteristics of scientific and professional terms, and terms related to various fields of science
Keywords: terms; terminology issues; historical terms